Enhancing learning outcomes in smart education: a supervised machine learning predictive analytics model for course completion - Abdellah Bakhouyi; Amine Dehbi; Lahcen Amhaimar; Yassine Tazouti; Younes Nadir; Abderrahim Khalidi (Institute of Advanced Engineering and Science, 2025)
Predictive analytics have become increasingly capable of delivering actionable and accessible feedback to enhance teacher performance to enhance student outcomes in higher education. This study introduces a supervised machine learning predictive model designed to forecast the duration required to complete a course in a video learning environment using a dataset of 8,665 statements from 490 students from National Higher School of Art and Design at Hassan II University in Casablanca over six academic years (2019-24). This paper analyzes decision trees (DT), random forest (RF), support vector machines (SVM), gradient boosting (GB), and linear regression (LR) techniques. The CMI-5 standard and JSON format are used to automatically transfer learning activity data from the learning management system (LMS) to the learning record store (LRS). The results indicate that DT, RF, and GB achieved 100 percent predictor accuracy.